Liberia : Request for a Four-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2019)
This paper highlights Liberia's Request for a Four-Year Arrangement Under the Extended Credit Facility. The program aims to support the authorities' strong adjustment efforts, catalyze significant donor financing, and provide a framework within which to implement the authorities' ambitious reform agenda. The authorities have demonstrated commitment by passing a credible budget for FY2020 that consolidates public finances, including by rightsizing the compensation of employees and implementing long-overdue comprehensive civil service reform, while protecting funds for critical social spending. The program also aims to catalyze substantial external support, which is critical to ensure that the programmed adjustment can be contained at levels that are politically and economically feasible while, at the same time, ensuring public and external debt sustainability. Ensuring financial sector stability is an important element of the program. Improving data reporting, obtaining an overview of the health of the banking system, and taking decisive measures as needed will help identify and address financial sector vulnerabilities. At the same time, enhancing the legal framework is important to ensure that the Central Bank of Liberia has the required instruments should remediation be necessary.